Investigating the number and type of literacy assessments and interventions in Aotearoa New Zealand primary schools. Issue 2 (3rd July 2022) - Arrow, Alison; Neville, Angela; Denston, Amanda; Nicholson, Tom
ABSTRACT: In Aotearoa New Zealand, the lack of government funding and support for interventions beyond Reading Recovery means that assessment and support for students demonstrating literacy difficulties are primarily left to schools themselves. To meet the needs of students, including those demonstrating difficulties with literacy learning, schools and teachers must have assessments and interventions that can identify and meet the needs of those students. Currently, there is a lack of research on the nature of assessments and interventions used by schools and their confidence in using these to meet the needs of students, including those with literacy learning difficulties. In the current study, we surveyed schools about the types of assessments used to identify literacy difficulties and the interventions provided to students. Results indicated a wide range of assessments and interventions used in schools, but the identified interventions often failed to meet the criteria for intervention (teacher-led, based on specific needs), and assessments were often unlikely to provide information about specific literacy difficulties. Overall, the variability of interventions and assessments indicated a lack of consistency in the identification of students with literacy learning difficulties and, in the interventions, provided to support these students.